2007
DOI: 10.1186/1477-7819-5-97
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the response of localised oesophageal cancer to neo-adjuvant chemoradiation

Abstract: Currently there are no clinically useful predictors of response based on standard pathological assessment and immunohistochemistry. Genomics, proteomics and molecular imaging may hold promise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 86 publications
0
7
0
1
Order By: Relevance
“…Transcriptional activation of P21/WAF1/CIP1, either p53‐dependent or independent, inhibits the accumulation of cyclin‐CDK complexes and, therefore, causes G1/S and G2/M arrest. The cell cycle arrest caused by P21/WAF1/CIP1 has also been shown to stimulate the cleavage of caspase 9 resulting in apoptosis within the cell (Gillham et al, ). We showed that fucoidan induced accumulation of P21/WAF1/CIP1 in APL cells.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional activation of P21/WAF1/CIP1, either p53‐dependent or independent, inhibits the accumulation of cyclin‐CDK complexes and, therefore, causes G1/S and G2/M arrest. The cell cycle arrest caused by P21/WAF1/CIP1 has also been shown to stimulate the cleavage of caspase 9 resulting in apoptosis within the cell (Gillham et al, ). We showed that fucoidan induced accumulation of P21/WAF1/CIP1 in APL cells.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, lehnert et al reported that gene chips could be used to survey radiation-associated genes (12). physicians explored different gene expression patterns between radiosensitive and radioresistant tumors in uterine cervical cancer (13), and to predict the clinical rt response in esophageal cancer (14) by microarray methods. However, the study of crc and radiation-associated gene expression is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiling and identification of molecular signature may hold promise for the future. 16,17 In our study, 63% of the patients (n = 23) showed evidence of gross residual tumor on resection specimen. Although 19 subjects in this group received R0 resection, the prognosis remained dismal.…”
Section: Discussionmentioning
confidence: 45%
“…In our study, we were unable to identify any significant pretherapy predictor of pCR in patients with cT2N0 disease. Gene expression profiling and identification of molecular signature may hold promise for the future 16,17 …”
Section: Discussionmentioning
confidence: 99%